Analysis of factors That Influence Buying Decisions in The Covid-19 Pandemi Era - Sarbullah Sarbullah; Yovita Mumpuni Hartarini; Tri Cahyadi (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
This study aims to determine Analysis of Factors That Influence Buying Decisions in The Covid-19 Pandemi Era (Case Study in Bear Brand Drinking Milk Beverage Products). This type of research was s quantitative correlation with a cross-sectional approach. Data collection techniques using questionnaires. The analysis technique used was multiple regression analysis. The independent variables were product quality, price, promotion, and testimonials and the dependent variable was buying decisions. Methods of data analysis using multiple linear regression with the SPSS 25.0 program. Based on the data analysis shows that: (1) It was found that the Product Quality variable (X1) in buying decisions (Y). It was known that the Sig value for the effect (X1) on (Y) was 0.211 > 0.05 and the tcount value was 1.262 < t table 2.000, so it can be concluded that H1 was rejected which means there was no effect (X1) on (Y). (2) Price (X2) on buying decisions (Y) It was known that the Sig value for the effect (X2) on (Y) was 0.913 > 0.05 and the tcount is-0.110 < t table 2.000, so it can be concluded that H1 was rejected which means there was no effect (X2) against (Y). (3) It was known that the Sig value for the effect (X3) on (Y) was 0.043 <0.05 and the tcount was 2.061 > t table 2.000, so it can be concluded that H1 was accepted which means there was an effect (X3) on (Y). (4) It was known that the Sig value for the effect (X4) on (Y) was 0.478 > 0.05 and the tcount was 0.714 < t table 2.000, so it can be concluded that H1 was rejected which means there was no effect (X4) on (Y). Product quality was needed to increase consumer attractiveness. The importance of optimizing affordable prices to be able to compete in the trade market. Attractive promotions can lure customers to always use the same product. Testimonials in an interesting manner by conveying relevant.